Against mereological nihilism - Tallant, Jonathan (Springer, 2013)
I argue that mereological nihilism fails because it cannot answer (what I describe as) the special arrangement question: when is it true that the xs (the mereological simples) are arranged F-wise? I suggest that the answers given in the literature fail and that the obvious responses that could be made look to undermine the motivations for adopting nihilism in the first place.